A brief appraisal of ethylene signaling under abiotic stress in plants. (1st September 2020) - Husain, Tajammul; Fatima, Abreeq; Suhel, Mohammad; Singh, Samiksha; Sharma, Anket; Prasad, Sheo Mohan; Singh, Vijay Pratap
ABSTRACT: For years, ethylene has been known to humankind as the plant hormone responsible for fruit ripening. However, the multitasking aspect of ethylene is still being investigated as ever. It is one of the most diversified signaling molecules which acclimatize plant under adverse conditions. It promotes adventitious root formation, stem and petiole elongation, opening and closing of stomatal aperture, reduces salinity and metal stress, etc. Presence of ethylene checks the production and scavenging of reactive oxygen species by strengthening the antioxidant machinery. Meanwhile, it interacts with other signaling molecules and initiates a cascade of adaptive responses. In the present mini review, the biosynthesis and sources of ethylene production, interaction with other signaling molecules, and its exogenous application under different abiotic stresses have been discussed.